Aspects of the relationship between heart rate and precision of throwing in wheelchair basketball. Preliminary study - Galea, Ioan; Dulceanu, Corina; Ungureanu, Oana (Arena-Journal of Physical Activities, 2019)
One of the most practiced disciplines for athletes with disabilities is wheelchair basketball. At the same time, in order to achieve the highest level of competitiveness, the specific training methods are based on experimental research made on the players of wheelchair basketball teams engaged in official competitions.The purpose of the study is to evaluate the precision of throwing (PoT) in relation to the player’s throwing position (TP), starting from the hypothesis that effort intensity, determined by heart rate (HR), could influence PoT.Methods. 5 athletes (My = 30.8 ± 7.5) members of the men’s wheelchair basketball team, national champion in 2009, participated in the study. A HOSAND system (Italy, 2005) was used for HR monitoring and, for the determination of the PoT, each player made 10 throws at the edge of the 3sec. quad from: 450 left, 450 right and from the free throw line for the 120 HR, 140HR, 160HR, and 180HR crossings.Conclusions. Within the limits of our study, the data obtained show that, for each player, the PoT depends on PT and is influenced by HR values. These data can be used by the coach to design training sessions that aim to improve basketball and to place players on the field on tactical pitch. However, data must be approached with caution because, in their assessment and capitalization, account must also be taken of each player’s competitive classification (IWBF functional classification).